2015
DOI: 10.1074/jbc.m114.597435
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Outer Pore Domain in Transient Receptor Potential Vanilloid 1 Dynamic Permeability to Large Cations

Abstract: Background:The TRPV1 ion channel alters its ionic selectivity in an activity-dependent manner. Results: Mutations in multiple subregions of the TRPV1 pore selectively augment or reduce large cation permeability changes. Conclusion: Side chain identities within the pore shape conformational changes underlying dynamic ionic selectivity. Significance: Understanding TRPV1 dynamic ionic selectivity will provide crucial insight into channel activation and nociceptive signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
7
36
1
Order By: Relevance
“…As a result, to adequately control the concentrations of ions when recording under bi-ionic conditions, the membrane conductance ( σ mem ) must be sufficiently small ( σ mem × R access ≪ 1; see Methods). The present results with P2X receptors, together with our reservoir model, provide sufficient motivation to reexamine the phenomenon of dynamic ion selectivity reported for TRPV1 channels 17, 18 , TRPA1 channels 47, 48 , ASICs 19, 20 , and TMEM16A calcium-activated Cl - channels 49, 50 . Dynamic ion selectivity for TRPV1 channels requires high agonist concentrations and high channel density 17 , and these channels have an appreciable permeability to NMDG + 17 and dyes 17, 40 , raising the possibility that ion depletion and accumulation may be responsible for the reported changes in ion selectivity of these channels.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As a result, to adequately control the concentrations of ions when recording under bi-ionic conditions, the membrane conductance ( σ mem ) must be sufficiently small ( σ mem × R access ≪ 1; see Methods). The present results with P2X receptors, together with our reservoir model, provide sufficient motivation to reexamine the phenomenon of dynamic ion selectivity reported for TRPV1 channels 17, 18 , TRPA1 channels 47, 48 , ASICs 19, 20 , and TMEM16A calcium-activated Cl - channels 49, 50 . Dynamic ion selectivity for TRPV1 channels requires high agonist concentrations and high channel density 17 , and these channels have an appreciable permeability to NMDG + 17 and dyes 17, 40 , raising the possibility that ion depletion and accumulation may be responsible for the reported changes in ion selectivity of these channels.…”
Section: Discussionsupporting
confidence: 66%
“…Voltage-activated potassium (Kv), sodium (Nav) and calcium (Cav) channels, for example, contain ion selectivity filters (containing ion binding sites) at the extracellular end of their pores 2, 3 that impart exquisite ion selectivity and enable them to play key roles in the generation and propagation of action potentials, or in excitation-secretion and excitation-contraction coupling 1 . However, a large number of studies on P2X receptor channels 4-16 , TRPV1 channels 17, 18 and ASICs 19, 20 have reported that ion selectivity can change dynamically in response to agonist activation. In the case of P2X receptors, the prevailing view is that the pore initially opens rapidly to a conducting state that is relatively selective for small cations (such as Na + , K + and Ca 2+ ), but then gradually dilates over time to become more permeable to large organic cations such as N-methyl-D-glucamine (NMDG + ), as well as to fluorophores as large as 14Å 4-16 .…”
mentioning
confidence: 99%
“…Specifically, a B30 amino acid loop connecting S5 with the pore helix, known as the pore turret ( Fig. 4a), has been implicated in channel gating, large organic cation permeation and pore dilation 33,34 . Mutation of key residues within the TRPV1 pore turret (Gly 618 and Ser 629), which are conserved in TRPV2 (Gly 582 and Ser 592; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…M644 is located in the selectivity filter, which is accomplished in the open state of the upper gate21. The mutation M644I was reported to decrease the permeability of NMDG for rat (r) TRPV123. I679 is located in the S6 segment of rTRPV1 protein and is suggested to be part of the lower gate2122.…”
Section: Resultsmentioning
confidence: 99%